3M: The Efforts to Give Understanding Early Childhood about Covid-19 - Anwar Zain; Sarimah (Universitas muhammadiyah Banjarmasin, 2022)
The purpose of this study was to explore how teachers introduce and explain Covid-19 including 3 M activities (wearing masks, washing hands and keeping a distance from crowds) to early childhood. The research method used qualitative-descriptive, the researchers conducted data mining by interviewing 24 PAUD teachers spread across the Barito Kuala District. Based on the results of the research that teachers provide an understanding of Covid-19 there are 4 aspects of the way that understanding is given, namely 1) how to provide an understanding of online learning, 2) how to provide an understanding of the use of masks, 3) how to provide an understanding of washing hands with soap, and 4) how to provide an understanding of keeping distance and not crowding.